Linguistic Equivalence, Construct Validity, But Lack Measurement Invariance: An Illustration of Challenges in Cross-Cultural Research on Adolescent Adjustment. (October 2020) - Tan, Tony Xing; Yi, Zhiyao; Kim, Eunsook; Li, Zhengjie; Cheng, Ke
In this study, we illustrated issues related to measure invariance in cross-cultural research involving instrument translation between Chinese and English. We translated and back-translated the third edition of the Behavioral Assessment for Children-Self Report of Personality (BASC-3-SRP) and administered it to 1, 574 youth in China and 512 youth in the United States. We found that despite a rigorous approach to achieving linguistic equivalence, statistically demonstrating acceptable internal consistency and construct validity, measurement invariance tests revealed that six of the 16 BASC-3-SRP subscales lacked measurement invariance. Constructs for the first three of the six subscales that lacked measurement invariance (i.e., Negative Attitude toward School, Negative Attitude toward Teachers, and Self-Esteem) are known to be conceptualized differently in collectivistic societies, while constructs for the second three subscales (i.e., Atypicality, Sense of Inadequacy, and Hyperactivity) lacked measurement invariance without known cultural reasons. These results highlight instrument development issues and measurement variance issues that cross-cultural researchers must grapple with.